Penolakan Hadis Ahad: Dari Mu'tazilah dan Jahmiyah hingga Tokoh Modern - Rafiq, Muhamad Chaedar; Kosasih, Engkos; Almighwar, Muhammad; Abdullah, Faiz; Fadllurrahman, Irfan (Darul Yasin Al Sys, 2024)
This study examines the crucial role of Hadith Ahad in Islamic teachings, both in matters of faith (aqidah) and other aspects. If Hadith Ahad cannot be used as a proof (hujjah), many Islamic teachings understood and believed by the majority of Muslims would be displaced. This consequence highlights the importance of understanding and accepting the authority of Hadith Ahad in maintaining the continuity and integrity of Islamic teachings. Rejection of Hadith Ahad would have a broad impact on the understanding and beliefs of the Muslim community. The Mu’tazilah and Jahmiyah are groups that understand religious sources by prioritizing reason, which naturally leads to differences with other groups. This study covers the definition of Hadith Ahad and its authority, the Mu’tazilah and Jahmiyah sects' rejection of Hadith Ahad, and discusses the modern scholars' rejection of Hadith Ahad, especially in the establishment of faith (aqidah).